2020
DOI: 10.3389/fphar.2020.01125
|View full text |Cite
|
Sign up to set email alerts
|

Biological Properties and Absolute Configuration of Flavanones From Calceolariathyrsiflora Graham

Abstract: Flavanones (-)-(2S)-5,4'-dihydroxy-7-methoxyflavanone (1) and (-)-(2S)-5,3',4'trihydroxy-7-methoxyflavanone (2) were isolated from the extracts of Calceolaria thyrsiflora Graham, an endemic perennial small shrub growing in the central zone of Chile. The absolute configuration of these compounds was resolved by optical rotation experiments and in silico calculations. Three analogs (3, 4, and 5) were synthesized to do structure-activity relationships with the biological assays studied. Biological tests revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The selection of this level is consequent to our previous study of both enantiomers of flavanone having natural isotopic abundances 27 for which we explored four levels of theory and found that all attempted calculations provided successful calculated spectra for good data comparison. By the way, the F I G U R E 1 Formulas of flavanones originally published VCD spectra of the flavanones with natural isotopic distribution were inadvertently wrong labeled in our initial study, 27 as it was recently already mentioned, 24 because the (S) labeled spectrum in reality corresponded to the (R) enantiomer and vice versa.…”
Section: Comparison Of Calculated and Experimental Vcd Spectramentioning
confidence: 79%
See 2 more Smart Citations
“…The selection of this level is consequent to our previous study of both enantiomers of flavanone having natural isotopic abundances 27 for which we explored four levels of theory and found that all attempted calculations provided successful calculated spectra for good data comparison. By the way, the F I G U R E 1 Formulas of flavanones originally published VCD spectra of the flavanones with natural isotopic distribution were inadvertently wrong labeled in our initial study, 27 as it was recently already mentioned, 24 because the (S) labeled spectrum in reality corresponded to the (R) enantiomer and vice versa.…”
Section: Comparison Of Calculated and Experimental Vcd Spectramentioning
confidence: 79%
“…Flavanone is the parent molecule of a well‐known series of aromatic secondary metabolites and is characteristic of citric fruits. It is mostly found in nature as the ( S ) enantiomer and only in a recent case a plant derived flavanone has been studied by VCD 24 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural characteristic that differentiates these compounds from the rest of the structures is the catechol group (1,2-dihydroxybenzene) in Ring B. Many known inhibitors of 5-LOX possess the catechol group that is a relevant characteristic for their inhibitory properties [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the spectra were carefully recorded several times over different days using correct operation conditions and the identity and purity of the samples were always checked by H-NMR measurements, so the mainly mono-signated spectra shapes seem to own the sample. In fact, the VCD spectra of 1 and 2 remember the spectra of 7- O - β -D-glucopyranosylchrysin, 21 of ( S )-5-hydroxy-7-methoxy-4’-acetyloxyflavanone, 22 and of podocephalol acetate. 23 For the later compound supramolecular studies could be done.…”
Section: Resultsmentioning
confidence: 99%